Retenção de caixa e liquidez nas companhias brasileiras: uma análise do período pré e pós-crise do subprime - Garbe, Hugo de Souza (2015)
The unusual keeper box is the tendency of companies to have greater liquidity. After the 2008 Subprime crisis, it was observed that some US companies retiam a greater amount of cash compared to pre-crisis period. This behavior was attributed , among several factors, the set of uncertainties in the economic and regulatory environment. The aim of this work is to incorporate research in the United States to the Brazilian reality , analyzing its grip on the national context. The population of interest in this study refers to non-financial companies listed on the São Paulo Stock Exchange . In this case we have 156 companies that comprise the initial sample . The study covers the years 2003 to 2013. Companies that were not traded during this period , were removed from the analysis. At this stage , the sample is 83 companies, which was reduced to 54 companies opened after a preliminary check of the data. The outbreak of the 2008 economic crisis , international markets found themselves in a situation of fragility , especially those who were not prepared in terms of financial regulation to address its effects. Economic crises encourage companies to have a higher level cash retention , since there is essentially a reduction in their levels of investment , reduction of credit in the financial market , and the effects of uncertainty about the future of the economy. The above authors analyzed the cash US companies during the crisis of 2001 and found that during the period there were cash retention, compared with previous periods. In this study, where the sample is comprised of companies with publicly traded on the São Paulo stock exchange , it was found in the data, that when comparing pre and post-crisis , there is a reduction of cash retention after 2008, which brings us to the conclusion that the economic crisis had a negative impact on companies surveyed.